A Review of The Main Global Developments Addressing Green Investments Among Central Banks Andreea OPREA - Andreea OPREA (Communications of International Proceedings, 2022)
Among the main reasons why there is a growing interest in ESG-type investments is the belief that sustainable investments bring a benefit in terms of portfolio risk management, and the growing recognition of the role of the financial sector in relation to ESG, given that climate change may pose a serious threat to financial stability. In the case of central banks, in general, the goal of sustainability can be integrated into the activity of managing reserves, without jeopardizing security and efficiency. The security and yield of green bonds support their incorporation into reserve portfolios, but some constraints could emerge in terms of accessibility and liquidity. Given the oversupply of green bonds in primary markets but reduced trading in secondary markets, the liquidity of green bonds may be limited, especially if investors keep these bonds to maturity. However, the persistence of excess demand should facilitate the sale of such assets, if necessary.
Keywords: ESG; central banks; green bonds; green investment; social responsibility; climate change